Causes of delay in residential construction projects in Cambodia. Issue 1 (1st January 2017) - Durdyev, Serdar; Omarov, Maksat; Ismail, Syuhaida
Abstract: Construction industry is one of the significant contributors to the economic growth and development of Cambodia. Two major challenges are limiting the performance of the construction industry in Cambodia, which are poor cost and schedule performance of the construction projects. Therefore, the aim of this study is to fill an important knowledge gap by identifying the various attributes for construction project delay, using the residential building projects as a starting point. Feedback from a survey administered to the contractors and consultants was analysed using Relative Importance Index (RII). Results showed that shortage of materials on site; unrealistic project scheduling; late delivery of material; shortage of skilled labour; complexity of project; labour absenteeism; late payment by the owner for the completed work; poor site management; delay by subcontractor; accidents due to poor site safety are ranked by the contractors and consultants as the main causes of project delays in Cambodia. Construction frontline players are recommended to put their efforts on the identified key factors in relation to their magnitudes of influence. By doing so, the causes of project delays in the Cambodia's construction and real estate sector could be significantly reduced or controlled, which will ultimately lead to the on time project completion.